16. yy'ın ilk yarısındaki divanlarda yavuz sultan Selim'e sunulmuş şiirler - (:unkn) unknown (My University, 2019)
Yavuz Sultan Selîm dokuzuncu Osmanlı padişahı olup 1512-1520 yılları arasındapadişahlık yapmıştır. Şehzadeliği ve padişahlığı döneminde çevresinde âlim, sanatkârve şair olmak üzere birçok kıymetli simanın yetişmesine imkân veren YavuzSultan Selîm çıktığı seferlerde de hocalarını ve şairleri musahip olarak yanında bulundurmaksuretiyle onlarla daima irtibat hâlinde olmuştur. Bu makalede; YavuzSultan Selîm döneminde klasik Türk şiirinde eser veren şairler taranarak divan sahibiolanlar belirlenmiş, elde bulunan divanlardan ve Mecmû‘a-i Kasâ’id-i Türkiyye’denYavuz’a ithafen şiir yazan şairler ve bu şairlerin şiirleri tespit edilmiştir. Selîmnâmetarzındaki müstakil eserler ve Yavuz adına yazılan mesneviler çalışmaya dâhil edilmemiştir.15.yy.ın sonu ile 16.yy.ın ilk çeyreğinde eser veren şairlerden Yavuz adınaşiir yazmış 16 şairin manzumesi muhteva bakımından incelenmiştir. Bu şiirlerdekihükümdarla ilgili benzetmeler ayrı bir başlık altında değerlendirilerek Yavuz’un hükümdarlığının,şairliğinin ve diğer özelliklerinin şiire yansıması hakkında bir sonucaulaşılmaya çalışılmıştır.

Selim I was the ninth Ottoman Sultan reigning from 1512 until 1520. During the term when he was a prince and a sultan, Selim I paved the way for the education of many venerable intellectuals, artisans and poets in his vicinity. He was always in contact with his tutors and poets and wanted to have them present as “musahip”s during his expeditions. In this article the poets having given divan (anthology of verse) to the classical Turkish poetry during Selim I’s reign have been searched thoroughly and the poets having a divan have been determined. From the divans on hand and from Mecmû‘a-i Kasâ’id-i Türkiyye the poets whose poems where dedicated to Selim I and the poetries of these poets have been ascertained. Distinct works in the style of Selîmnâme and masnavis which where written in the name of Selim I have not been added to this workout. The content of the poems belonging to 16 poets who made works in the name of Selim I at the end of the 15th century until the first quarter of the 16th century have been worked through. The analogies regarding the sultan in these poems have been worked up under another heading. We tried to determine how the sultanate of Selim I, his poesy and his other characteristics reflected on the classical Turkish poetry.
“The Poems Presented To Selım I ın The Dıvans of The Fırst Half of The Sıxteenth Century”
Keywords: Antropoloji